Harvest residues management and silvicultural operations impact on soil physical and organic matter quality of eucalypt plantations - Ferreira, Gabriel William Dias (2017)
Brazil is among the world’s largest timber producers and Eucalyptus planted forests are responsible for a significant portion of wood products supply. Furthermore, these forests play an important role on mitigation of increasing atmospheric greenhouse gases. The period between harvesting and new rotation establishment, i.e. its first two or three years, concentrates the major part of forest mechanical operations that may define achievable productivity while causing harmful impacts on soil physical and organic properties. This thesis is divided in three chapters that evaluated and tried to provide a better understanding of these operations impact on eucalypt forest dynamics and soil properties. The first chapter approached how the management of eucalypt harvest residues (HR) could alter its decomposition pattern and the dynamics of two soil organic matter (SOM) fractions (Particulate Organic Matter – POM, and Associated to Minerals – MAOM). The experiment was set up in an area where natural grasslands of Pampa Biome in the Rio Grande do Sul State, Brazil, have been recently converted to eucalypt forests. Removal of all residues (-R), only bark removal (-B) and maintenance of all residues (+B), all of them combined with external 200 kg ha -1 of N addition (+N) or not (-N), were simulated in PVC micro-plots in a 3x2 full factorial with 4 replications. A 10 % 15 N-enriched solution was used as N source to track the role of mineral-N in the process. Whole micro- plots were sampled at 0, 3, 6, 12 and 36 mo. after experiment establishment and taken to the lab for further analysis. All sampling times were used to build decomposition curve, while C, δ 13 C, N and 15 N content associated with both SOM fractions were determined on 36 mo. samples in 0 -1 and 1 -5 cm soil layers. In these same layers, SOM fractions from 12 and 36 mo. samples were characterized with Pyrolysis associated with Gas Chromatography/Mass Spectrometry (Py-GC/MS) to obtain a better understanding of SOM formation pathway under different HR management. Almost 80 % of HR have been decomposed until 3 yr. Bark (p<0.05) and mineral-N (p=0.06) presence slowed down decomposition. Overall, changes in C and N content and δ 13 C due to residues presence were more expressive in 0-1 cm layer and POM fraction. +B tended to increase HR contribution, but its effect was more distinguished in -N treatments. Mineral-N fraction was always higher when HR were present, particularly in +B treatments, but its contribution to SOM fractions was always smaller than 4 %. Py-GC/MS products revealed a direct role of HR on POM formation, but their effect on MAOM seems to be indirect by altering microbial composition and its products. In summary, we showed how HR management drives SOM fractions chemistry and we conclude that a sustainable management of HR can enhance soil C accrual. In the second chapter was evaluated how two different harvest systems would change soil physical properties, soil C content and soil CO 2 efflux, and initial tree growth under two different silvicultural system. To this end, two adjacent stands located in Estrela do Sul/MG were selected. Each stand was harvested and logged with a different system (Feller + Forwarder – F+F; and Feller + Skidder – F+S) and soil physical properties [Soil Bulk Density (Ds), Micro (Mi), Macro (Ma) and Total Porosity (TP), and Penetration Resistance (PR)], SOM properties [Labile- C, C associated with Particulate (C-POM) and Mineral (C-MAOM) fractions] soil CO 2 efflux and stump mortality rate, were assessed after harvesting operations and compared with reference (before harvesting). Afterwards, each stand was divided in coppice and replanting, and we followed soil CO 2 efflux after planting and one year after planting, when trees height (H) and SOM properties were also measured in both areas and system to evaluate how areas would recover from harvesting impacts. All soil variables were assessed at planting and inter-planting row positions. Both systems affected soil density and soil pore configuration, but in different ways. F+F concentrates traffic at inter- planting row position, and therefore causes a slightly higher compaction in this region, while F+S does not follow traffic routes and impacts planting-row similarly, resulting in higher stump mortality. Harvesting operations increased Ds, Mi and PR and reduced Ma and TP at all layers. Soil CO 2 efflux was not affected by harvesting operations. Differences in soil CO 2 were found after planting, when it was higher in F+S system, that also presented higher labile-C and C-POM. One year after planting, mortality rate was still higher under coppice in F+S system, that also presented lower trees. In turn, trees were higher in replanting in this area. Soil respiration behaved similarly, i.e., higher in F+F under coppice and lower under replanting. Overall, after one year coppice system presented higher Labile-C, C-POM and C-MAOM. We concluded that each harvest system affects row and inter-row differently, creating different soil functional zones inside same area, that might be enhanced by the next silvicultural system chosen, and should be observed when assessing ecosystem services and site condition. Lastly, the third chapter evaluated the effect of land use change from natural grasslands of Pampa Biome to eucalypt plantations, as well as N fertilization effects on initial eucalypt growth, fine-root biomass (FRB) and its spatial distribution, and C, δ 13 C and N content associated with SOM fractions (POM and MAOM). 4 N-levels were tested (24, 36, 48 e 108 kg ha^-1 of N) on initial tree growth (until 2 yr.). Afterwards, representative trees were chosen to evaluate FRB until 40 cm depth, and soil samples also until 40 cm depth were collected for SOM evaluation. Positive effect of N on tree growth (diameter and height) was seen initially after fertilization, i.e., 1.5 yr., whereas at 2 yr. N effects were seen only at trees height. The FRB fitted regression showed increase of FRB until 56 kg ha^-1 of N, and after that level a decrease in FRB was observed, and the highest N level used resulted in the lowest FRB. Both horizontal and vertical anisotropy in fine-root distribution were observed, and besides differences among N levels, we could not see a clear relation between N fertilization and fine-root spatial distribution. Overall, land use change to eucalypt plantations increased soil C content, particularly in top-soil layers. 36 kg ha^-1 resulted in higher C-POM in 0 -10, while 48 kg ha^-1 resulted in higher C-MAOM in this layer. C and N dynamics were tightly correlated, especially in MAOM fraction. C-POM was positively correlated with FRB. Tillage had a strong control on soil C and N stocks, enhancing C deposition and turnover at row (ridge) region, most likely for favoring roots development in this region. Therefore, it is shown that N fertilization may alter initial tree growth, but its effects don’t seem to last longer. Nevertheless, N effects can be reflected on fine-root biomass and distribution and C and N of SOM fractions. We hope that our findings could guide the adoption of proper management practices in eucalypt plantations in Brazil, enhancing the productivity and sustainability of these forests.